Algorithm for detecting late swing using only acceleration in the direction of travel of the foot - Atsuki TSUBOI; Taku ITAMI; Jun YONEYAMA (Nihon Kikai Gakkai ronbunshu, 2022)
If an abnormality occurs while walking and a fall occurs, elderly people with reduced muscle strength and bone density may become bedridden in the worst case due to a fracture of the neck of the femur. The purpose of this study is to develop an algorithm that detects late swing using only from the acceleration in the direction of travel for the purpose of preventing falls during walking. In this study, the late swing detection algorithm is proposed to detect from the rate of change of the traveling direction acceleration. We used motion capture system to confirm whether the discrimination late swing is detected the point between the maximum speed of the foot and the heel strike. From the results, the late swing in 88% to 98% of the gait cycle was detected using the proposed algorithm.